Hello from MrBillDoesMath!
Answer: 14.75330052 ...
Discussion: Per the author the equation should be interpreted as
3 ^(x+1) = 5^ (x-4)
NOT as (3^x) + 1 = (5^x) -4
Rewrite the equation to pull out the constant terms:
3^(x+1) = 3^x * 3^1 = 3^x * 3 = 5^x * (5^-4)
so 3^x * 3 = 5^x * (5^-4)
Divide both sides by 3 to get
3^x * = 5^x * ((5^-4) / 3)
Divide both sides by 5^x to get
(3/5) ^ x = ( 1/625 * 1/3) = 1/1875
Take the base 10 logarithm (is this middle school math?) of each side
x * log(3/5) = log (1/1875) or (taking log. bring exponent down)
x = log(1/1875) / log (3/5)
so
x = (-3.273001272 )/ -0.22184875
which gives x as approx 14.75
I suspect there is still something wrong in the problem statement as I'm skeptical that this is middle level math.
Regards, MrB